Analysis of urine pH measurement using Arduino UNO-based pH Sensor - Achmad Safii; Muhammad Ghozali (Journal of Holistic Medical Technologies (JHMT), 2025)
Naturally, humans possess excretory organs that function to eliminate metabolic waste products. Urine is one of the fluids resulting from metabolic waste in the body. Urine can serve as an indicator of actual body condition. Urine pH measurement is one of the easily accessible methods for determining the body's acid-base balance. The pH meter system for urine pH detection was constructed using a pH V1.1 sensor as hardware with Arduino Uno assistance as both hardware and software for program processing. This research focuses on designing a device to determine urine pH levels using the Research and Development (R&D) pH meter method. Device calibration using buffer solutions with pH values of 4.01, 6.86, and 9.18 yielded a device error value of 0.11% and standard deviation (S) = 0.0091. Testing was also conducted using 30 human urine samples from subjects aged 16 to 40 years. The tested urine samples were 100 ml each, with results showing pH values ranging from 4.86 to 6.97. The standard deviation (S) for urine sample testing was 0.081. The difference in standard deviation values between calibration and urine samples was attributed to probe cleanliness on the pH meter, emphasizing the importance of probe cleanliness when switching between samples.